2021
DOI: 10.1073/pnas.2013925118
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of bacterial motility in microfluidics-confining environments

Abstract: Understanding the motility behavior of bacteria in confining microenvironments, in which they search for available physical space and move in response to stimuli, is important for environmental, food industry, and biomedical applications. We studied the motility of five bacterial species with various sizes and flagellar architectures (Vibrio natriegens, Magnetococcus marinus, Pseudomonas putida, Vibrio fischeri, and Escherichia coli) in microfluidic environments presenting various levels of confinement and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 95 publications
0
39
0
Order By: Relevance
“…As a result, a growing number of studies describe active particles using run-and-tumble dynamics, and results obtained with bacteria may be applicable to other systems as well. Furthermore, the use of different bacterial species and genetic mutants enables the study of cells of diverse other motility behaviors, shapes, sizes, and surface chemistries, which provides a means to explore a broad range of microswimmer properties 4,6,11,[35][36][37][38][39] . Thus, studies of bacterial transport in complex environments can provide useful fundamental insights into the dynamics of active matter more broadly.…”
Section: Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a growing number of studies describe active particles using run-and-tumble dynamics, and results obtained with bacteria may be applicable to other systems as well. Furthermore, the use of different bacterial species and genetic mutants enables the study of cells of diverse other motility behaviors, shapes, sizes, and surface chemistries, which provides a means to explore a broad range of microswimmer properties 4,6,11,[35][36][37][38][39] . Thus, studies of bacterial transport in complex environments can provide useful fundamental insights into the dynamics of active matter more broadly.…”
Section: Bacteriamentioning
confidence: 99%
“…Furthermore, we note that many bacteria self-propel through other mechanisms, such as by swarming or pulling themselves on surfaces 39 -which potentially enables them to sense mechanical cues on surfaces 42 and thereby respond to a broader range of stimuli. Investigating these other forms of active transport in complex environments is another important area of current research 35 . Finally, motivated by rapid progress in the synthesis of colloidal microswimmers capable of recapitulating many of the features of bacteria 43 , we also integrate references to studies of synthetic microswimmers throughout this section where relevant.…”
Section: Bacteriamentioning
confidence: 99%
“…Therefore, design and dimension of supply channel, cultivation chamber, and the chamber's entrance always represents a tradeoff between optimal nutrient supply and sufficient cell retention. Especially for the long-term cultivation of slow growing cells 11 as well as the microfluidic cultivation of motile cells 12 , a reliable cell retention concept is a fundamental requirement to prevent permanent cell loss, which otherwise compromises qualitative and quantitative cell studies.…”
mentioning
confidence: 99%
“…Physical confinement is one important factor that bacteria commonly face during motility, and confinement effects can profoundly alter their trajectory and migration patterns (17); nevertheless, this factor is explicitly excluded from open-space swimming measurements. Even under moderate levels of confinement, swimming microorganisms have been observed to accumulate near a solid surface, produce circular trajectories, and scatter from obstacles (15,18). Recent work revealed that even between bacteria with similar flagellar organizations, there are large variations in swimming tendencies, especially with regards to surface association and confined movement (18).…”
mentioning
confidence: 99%
“…Even under moderate levels of confinement, swimming microorganisms have been observed to accumulate near a solid surface, produce circular trajectories, and scatter from obstacles (15,18). Recent work revealed that even between bacteria with similar flagellar organizations, there are large variations in swimming tendencies, especially with regards to surface association and confined movement (18). The drastic changes in the behavior of confined bacteria as well as the underlying physical mechanisms are not well understood, and highlight that open space swimming characterizations will often not accurately generalize to swimming in other physical conditions.…”
mentioning
confidence: 99%